COVID-19 PANDEMIC: TEACHER PROBLEMS - EARLY CHILDHOOD LEARNING (PAUD) - THE SOLUTION - Darmayanti, Rani; Arian Sah, Retno Wahyu; Azizah, Isnaini Nur (Jurnal Caksana : Pendidikan Anak Usia Dini, 2021)
The impact of the COVID-19 pandemic is quite serious and occurs in almost all parts of the world, including in the education sector. The purpose of this research is to find out what are the obstacles teachers at PAUD YALC Pasuruan have in the early childhood learning process during the Covid 19 pandemic. The methodology used in this research is a qualitative case study. The data collection method in this study was to collect information using various qualitative research data collection procedures, by way of interviews and observation. The results found were 1) learning during the Covid-19 pandemic for early childhood at PAUD YALC Pasuruan, namely using distance learning by means of teachers making video calls to students to provide learning activities, 2) parents of students every Monday must take media that has been prepared at school to help learning in children, 3) the teacher makes interesting videos for children through supporting applications and then uploads them to social media such as YouTube, and 4) learning with a home visit system, home visits are teacher activities visiting the house all students once a week, this activity helps the teacher in seeing developments in children including their motor development. The obstacles found are 1) teachers are required to master technology such as supporting applications to display interesting videos and be watched by children, 2) assessment and evaluation of child development that are not optimally carried out by teachers, and 3) personal ownership of communication devices (cellphones) child, the tool belongs to the parent which is used by the parents as a work support tool.